2017
DOI: 10.5194/gmd-10-2221-2017
|View full text |Cite
|
Sign up to set email alerts
|

rpe v5: an emulator for reduced floating-point precision in large numerical simulations

Abstract: Abstract. This paper describes the rpe (reduced-precision emulator) library which has the capability to emulate the use of arbitrary reduced floating-point precision within large numerical models written in Fortran. The rpe software allows model developers to test how reduced floating-point precision affects the result of their simulations without having to make extensive code changes or port the model onto specialized hardware. The software can be used to identify parts of a program that are problematic for n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…We also demonstrated that the same basic approach can be applied to a real land surface scheme, using high precision for storing and updating state variables and lower precision for the remaining computations, to achieve a forecast that is within desired accuracy limits. This mixed-precision approach is likely generally applicable to many Earth system model components, and has been demonstrated in other areas (e.g., Düben et al 2017;Dawson and Düben 2017). These results combined suggest that even when it appears lower precision may present problems, it could be possible to continue doing the majority of computations using lower precision and just use higher precision for selected computations that are particularly sensitive to precision.…”
Section: Discussionmentioning
confidence: 72%
“…We also demonstrated that the same basic approach can be applied to a real land surface scheme, using high precision for storing and updating state variables and lower precision for the remaining computations, to achieve a forecast that is within desired accuracy limits. This mixed-precision approach is likely generally applicable to many Earth system model components, and has been demonstrated in other areas (e.g., Düben et al 2017;Dawson and Düben 2017). These results combined suggest that even when it appears lower precision may present problems, it could be possible to continue doing the majority of computations using lower precision and just use higher precision for selected computations that are particularly sensitive to precision.…”
Section: Discussionmentioning
confidence: 72%
“…We use the default of double precision, the new number format, or reduced floating point precision to levels lower than single precision. The latter simulations use the so‐called rpe reduced precision emulator described in Dawson and Düben () to mimic a reduction in floating point precision.…”
Section: Resultsmentioning
confidence: 99%
“…This would reduce the number of bits required for the significand further. However, even with the two changes applied for simulations (as presented in Dawson & Düben, ), differences between the standard model and a model simulation in half precision with 16 bits per variable are visible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further verify our methods, simulations were also conducted with 16-bit floating-point numbers, which is referred to as half precision by the IEEE 754 standard. Because precisions lower than 32 bits are generally unavailable from the computer systems and Fortran compilers EAMv1 is supported for, the reducedprecision emulator from Dawson and Düben (2017) was used. For each emulated half-precision number, 5 of the 16 bits were used for the exponent and 1 for the sign, leaving 10 bits for the mantissa, hence the half-precision number only had three to four accurate decimal digits.…”
Section: Introducing Reduced Precision To Eamv1mentioning
confidence: 99%